Assessment of Gliflozins prescribing pattern in a United Arab Emirates tertiary-level care hospital - Shenouda, Wessa; Thomas, Dixon; Nabi, Omar; Zachariah, Seeba (Frontiers in Pharmacology, 2025)
BackgroundSodium-Glucose Co-Transporter 2 (SGLT2) inhibitors, known as Gliflozins, have demonstrated efficacy in managing type 2 diabetes mellitus (T2DM) and providing cardiovascular and renal benefits. Given the prevalence of diabetes, heart failure (HF), and chronic kidney disease (CKD) in the UAE, there is a need to evaluate the prescribing patterns of Gliflozins in these population. The objective of this study was to explore the relationship between Gliflozins use for patients who were admitted to the hospital at least once from 2021 to 2023 and different clinical factors.MethodsA retrospective medication review was conducted from 2021 to 2023 at tertiary-level care hospital in Ajman, UAE. Data were collected on prescribed Gliflozins, patient demographic information, BMI, HbA1c levels, and comorbidities (HF, CKD). Chi-square tests and binary logistic regression were used to explore associations between Gliflozin use and clinical factors.ResultsOut of the 255 patients’ data collected, Gliflozin use was significantly associated with obesity (p = 0.002), higher HbA1c levels (p < 0.001), and comorbidities, particularly HF (61.5% of HF patients) and CKD. The use of Gliflozins increased each year. Patients with HF were 8.03 times more likely to use Gliflozins, and those with diabetes were 6.86 times more likely, underscoring the multidimensional role of these medications.ConclusionGliflozin prescribing patterns in the UAE reflect global trends, with increased use among patients with diabetes, HF, and CKD. Further research is recommended to explore factors influencing prescription practices and optimize Gliflozin therapy if gliflozins use considerably increase in new diagnosis of diabetes and CKD even in mild conditions.